A Vanished Arcadia: Being Some Account of the Jesuits in Paraguay 1607-1767 - Cunninghame Graham, R. B. (Robert Bontine), 1852-1936 (Salt Lake City, UT : Project Gutenberg, 1998)
"A Vanished Arcadia: Being Some Account of the Jesuits in Paraguay 1607-1767" by R. B. Cunninghame Graham is a historical account written in the early 20th century. The work delves into the history and influence of the Jesuits in Paraguay, focusing specifically on their interactions with the indigenous populations and the socio-economic conditions during their time in power. The opening of the text sets the tone for a reflective exploration of the Jesuit missions in Paraguay, cast against the backdrop of the author's personal memories and observations. Cunninghame Graham acknowledges his lack of formal preparation for this historical task, yet he is inspired by vivid recollections of the region's landscapes and the Jesuit legacy. He expresses a deep appreciation for the ecclesiastical efforts that established a quasi-communal society among the Indigenous people, while simultaneously grappling with the controversies surrounding the Jesuits, their motivations, and the contrasting narratives that emerged after their expulsion. His narrative hints at themes of nostalgia and melancholy as he sketches a portrait of the prosperous Jesuit rule, which he believes eventually gave way to chaos and decline following their departure. (This is an automatically generated summary.)
Release date is 1998-10-01
Alan Robert Light
Keywords: Jesuits -- Paraguay; Paraguay -- History -- To 1811